Determinants of CTS Complaints on Sorting Workers atTalang Gulo Landfill, Jambi City - Maria Fransiska Choagolan; Hubaybah .; Budi Aswin; Oka Lesmana; Fitria Eka Putri (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Epidemiologically, Carpal Tunnel Syndrome (CTS) has symptoms such as pain, numbness or loss of sensation in the hands and tingling or feeling of needle puncture on the wrist. Sorting workers are workers who are at risk of developing complaints of Carpal Tunnel Syndrome (CTS). The purpose of this study is to determine the relationship between factors related to complaints of Carpal Tunnel Syndrome (CTS) in sorting workers at the Talang Gulo Landfill, Jambi City in 2022. This study used cross-sectional design quantifiable research. The population is all sorting workers in the sorting area of the Talang Gulo landfill in Jambi City totaling 34 people. The sample of this study was 29 respondents. . The analysis test used is the chi-square test.The results showed that respondents who experienced CTS complaints were 55.2%. The bivariate test results had a relationship between PR 7.89 age (95%CI 1.21-51.4), PR 3.05 repetitive movement relationship (95%CI 1.10-8.43), and there was a PR 2.43 working posture relationship (95%CI 1.02-5.77) with CTS complaints in sorting workers. There was no relationship in nutritional status of PR 0.74 (95%CI 0.35-1.56). The variable length of work cannot be carried out the analysis test because the results of the univariate analysis test are homogeneous.